Intragenic CAMTA1 rearrangements cause non-progressive congenital ataxia with or without intellectual disability. Issue 6 (12th June 2012) - Thevenon, Julien; Lopez, Estelle; Keren, Boris; Heron, Delphine; Mignot, Cyril; Altuzarra, Cecilia; Béri-Dexheimer, Mylène; Bonnet, Céline; Magnin, Eloi; Burglen, Lydie; Minot, Delphine; Vigneron, Jacqueline; et al.
Abstract : Background: Non-progressive congenital ataxias (NPCA) with or without intellectual disability (ID) are clinically and genetically heterogeneous conditions. As a consequence, the identification of the genes responsible for these phenotypes remained limited. Objective: Identification of a new gene responsible for NPCA and ID. Methods: Following the discovery of three familial or sporadic cases with an intragenic calmodulin-binding transcription activator 1 ( CAMTA1 ) rearrangement identified by an array-CGH and recruited from a national collaboration, the authors defined the clinical and molecular characteristics of such rearrangements, and searched for patients with point mutations by direct sequencing. Results: Intragenic copy number variations of CAMTA1 were all located in the CG-1 domain of the gene. It segregated with autosomal dominant ID with non-progressive congenital cerebellar ataxia (NPCA) in two unrelated families, and was de novo deletion located in the same domain in a child presenting with NPCA. In the patients with ID, the deletion led to a frameshift, producing a truncated protein, while this was not the case for the patient with isolated childhood ataxia. Brain MRI of the patients revealed a pattern of progressive atrophy of cerebellum medium lobes and superior vermis, parietal lobes and hippocampi. DNA sequencing of the CG-1 domain in 197 patients with sporadic or familial non-syndromic intellectual deficiency, extended to full DNA sequencing in 50 patients with ID and 47 additional patients with childhood ataxia, identified no pathogenic mutation. Conclusion: The authors have evidence that loss-of-function of CAMTA1, a brain-specific calcium responsive transcription factor, is responsible for NPCA with or without ID. Accession numbers: CAMTA1 reference sequence used was ENST00000303635. Protein sequence was ENSP00000306522.